Analysis of Anxiety Levels in South Sulawesi Provincial Football Referees - SAHARULLAH; FAHRIZAL; AMIN , Nursalehuddin (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
This study is a quantitative descriptive study that aims to measure the level of anxiety in football referees of the Provincial Association of Indonesian Football Associations, South Sulawesi. One independent variable in this study was the level of anxiety of football referees in the Provincial Association of the All Indonesia Football Association of South Sulawesi Province. The population in this study is all football referees of the Provincial Association of the All Indonesia Soccer Association of South Sulawesi. While the sampling technique uses purposive sampling techniques, the samples used are 25 football referees in South Sulawesi. Based on the results of the analysis, it can be concluded that the level of empathy is 3 respondents 12% in the low category, 7 respondents 28% in the sufficient category, 11 respondents 44% in the good category, and 4 respondents 16% in the very good category. This research needs further review on factors of knowledge, motivation, and physical components.